Adult learning in the language classroom - Johnson, Stacey Margarita (New Perspectives on Language and Education, 2015)
This book explores connections between the fields of foreign/second language teaching and adult learning. This interdisciplinary approach serves as a framework in order to: (a) understand the teaching methods that promote the deeper, more critical sort of language learning advocated by scholars and professional organizations, (b) understand how adult students learn and transform through language study, and (c) reinforce the immense value of beginning language courses. Johnson studies a classroom of adult language learners for one semester, exploring issues of motivation and perceived value for these short-term learners as well as touching on issues around intercultural communication teaching and learning. The book will be of interest to adult language teachers as well as researchers studying adult education and second language learning